Autonomy in Decision-Making Processes and Forms of Control: A Study Based on Adorno's Negative Dialectics with Technology Professionals - Ferreira, Tiago Henrique; Carvalho Neto, Antônio; Diniz, Daniela Martins (Revista de Administração da UFSM, 2025)
Purpose: Do technology companies truly adopt horizontal management models? This study aimed to analyze the level of autonomy of individuals in the decision-making process within technology companies, identifying forms of control and contradictions in the interviewees' discourses, through the lens of Adorno's Negative Dialectics. Methodology: The interviewees consisted of 16 professionals working in technology companies, occupying various positions such as founder and partner, CEO, manager, analyst, software developer, among others. Findings: The results indicate, firstly, that even in organizations characterized by higher levels of horizontal management, where greater autonomy of individuals is presumed, some form of "authority" is still observed. The data also reveal that the autonomy of individuals in these technology environments is closely related to the technical competence of the professionals in their respective fields. Finally, it was found that some managers advocate for the autonomy of their employees but still seek to maintain control through various mechanisms, such as budget centralization; management by objectives; creation of formal and standardized structures; and attempts to copy and replicate American management models adopted by companies in Silicon Valley. Originality: In the national literature, there was no national study that sought to analyze horizontal management in the context of technology companies from the perspective of Adorno's Negative Dialectics. In this sense, this study was able to promote a deeper and more critical analysis of the dynamics of power and authority within technology organizations.